Democrats, mediocre and technicians. The tensions of the university future in Peru - Lynch, Nicolás (2019)
The current article explains the relatinonship between the lack of State support, faculty mediocrity, democratic reason and technochratic reason in the Peruvian university in the last century. It presents the sequence of logic and conflict between the different discourses in the process of reform of higher education starting with the university movement in Córdoba, Argentina in 1918 to the present times. The article highlights the formation of democratic reason in the different moments of crisis and change in the university and states that this kind of reason is the possibility of giving a future to the production of knowledge in Peru.